Formation of i-motifs from acyclic (l)-threoninol nucleic acids. Issue 33 (30th July 2019) - Kumar, Vipin; Nguyen, Thuy J. D.; Palmfeldt, Johan; Gothelf, Kurt V.
Abstract : Acyclic (l )-threoninol nucleic acids ((l )-aTNA) containing poly-cytosines are prepared and investigated at various pH values, revealing the formation of a highly stable structure at lower pH that have the characteristics of an i-motif. Abstract : Acyclic (l )-threoninol nucleic acids ((l )-aTNA) containing poly-cytosines are prepared and investigated at various pH values, revealing the formation of a highly stable structure at lower pH that have the characteristics of an i-motif. Depending on the sequence, the aTNA forms inter-, bi- and intra-molecular i-motif structures. Pyrene was conjugated to aTNA sequences and both monomeric and excimer fluorescence were efficiently quenched by the i-motif structures and thus demonstrated that the aTNA i-motif can serve as a pH switch.